XMU-MP-1 attenuates osteoarthritis via inhibiting cartilage degradation and chondrocyte apoptosis - Hao, Xue; Zhao, Jing; Jia, Liyuan; He, Ting; Wang, Huanbo; Fan, Jing; Yang, Yating; Su, Fei; Lu, Qingda; Zheng, Chao; Yang, Liu; Jie, Qiang (Frontiers in Bioengineering and Biotechnology, 2022)
Osteoarthritis (OA) is the most prevalent type of degeneration joint disease, which is reported to be associated with inflammatory responses, chondrocyte apoptosis and cartilage degeneration. XMU-MP-1 is a selective MST1/2 inhibitor thereby activating the downstream effector YAP and promoting cell growth, which displayed excellent benefits in mouse intestinal repair, as well as liver repair and regeneration. However, the effects of XMU-MP-1 on OA remain unclear. In this study, we investigated the therapeutic role of XMU-MP-1 on interleukin-1β (IL-1β)-induced inflammation in mice chondrocyte and the destabilization of the medial meniscus surgery (DMM)-induced OA model. In chondrocytes, treatment with XMU-MP-1 rescued the elevation of matrix metalloproteinases (Mmp3, Mmp13) and decrease of extracellular matrix (Col2, Acan) induced by IL-1β. Moreover, XMU-MP-1 strongly inhibited IL-1β-induced chondrocyte apoptosis and significantly promoted chondrocyte proliferation. Furthermore, XMU-MP-1 showed a protective and therapeutic influence on the mouse OA model. To sum up, these findings indicate that XMU-MP-1 may exert a protective effect on cartilage degradation and maybe a new potential therapeutic option for OA.